Exploring Transitivity in Cinderella Story: Analyzing Participants, Processes, and Circumstances - Cindy Winda Mareta (Universitas Pembangunan Nasional “Veteran” Jawa Timur, 2000)
Using the framework of Systemic Functional Linguistics (SFL), this study investigates the transitivity system in narrative texts with a particular focus on Cinderella Story. Collaborating participants, processes, and circumstances in language to communicate meaning is transitivity. The study explores how actors, aims, and sayers build the story along with material, mental, and relational processes emphasizing actions, emotions, and relationships. Time, location, and cause are circumstantial components that improve the story and bring the reader to significant moments. According to the research, circumstantial components of time and place create the story's unknown and timeless state of mind, but material processes survive and reflect the action-driven nature of the narrative. Participants emphasize the relationships between power and character transformation, such as Cinderella as the actor and the Prince as both actor and objective. In addition to creating the narrative, these linguistic components reflect latent ideas, cultural norms, and societal values. The theoretical and educational consequences of transitivity analysis are emphasized in this article. Demonstrating how narratives create meaning improves linguistic theory and provides educators useful tools to enhance their students' critical text comprehension. This study shows how transitivity in educational methods can foster greater engagement with stories and an understanding of their underlying social and cultural elements.